Counseling services and academic resilience among university students: a systematic literature review of intervention modalities and mechanisms - Rina Efiana; Netrawati Netrawati; Herman Nirwana; Nurfarhanah Nurfarhanah (Indonesian Institute for Counseling, Education and Theraphy, 2026)
Academic resilience, defined as students' ability to remain academically engaged and adapt effectively despite academic, social, and psychological challenges, has become an increasing priority for universities. Counseling services including individual, group, digital, and curriculum-embedded interventions are widely implemented to strengthen resilience, yet evidence regarding their effectiveness remains limited. This systematic review aimed to synthesize evidence on the impact of counseling services on university students' academic resilience. Following the PRISMA 2020 guidelines, a Boolean search was conducted in the Scopus database, identifying 766 English-language publications published between 2020 and 2026. After screening and eligibility assessment, 60 articles met the inclusion criteria. Quality appraisal using the FICO framework (minimum score of 5/8) resulted in 10 studies being included in the qualitative synthesis. Four major themes emerged: (1) group counseling using cognitive behavioral and acceptance-based approaches effectively enhanced resilience and reduced psychological distress; (2) individual counseling through university counseling centers promoted self-acceptance and decreased clinically significant distress over time; (3) digital and app-based counseling expanded accessibility but showed more variable effectiveness than face-to-face interventions; and (4) embodiment- and nature-based therapies demonstrated promise as complementary approaches. Overall, counseling services positively contribute to students' academic resilience, with psychological interventions serving as the primary mechanism for improving resilience outcomes. These findings provide practical guidance for universities in optimizing counseling services. However, the review was limited to a single database, English-language publications, and a single-reviewer screening process, highlighting the need for future multicenter studies comparing counseling modalities and intervention characteristics.